Menghayati Kembali Iman Kristen Lewat Anateisme - Suarbudaya Rahadian (Indonesian Journal of Theology, 2015)
With this essay, I aim to provide an alternative way of embracing Christian faith in this postmodern era, by considering both Richard Kearney's concept of anatheism as well as Slavoj Zizek's radical materialism. With the death of the God of ontotheology—as accomplished by modern atheism—Kearney posits anatheism to desribe a further experience of faith that "rebounds" back to God. As such, it assumes a new dimension of encounter with (a/the) postonthotheological God by means of a "wager of faith." In contrast to this God-ward return, the radical materialism of Slavoj Zizek’s theological approach foregrounds the very absence of an "absolute-yet- fragile" God within secular, public space. This paper will outline also my own proposal for leveraging nihilism as constructive dialectic for refining and amplifying Christian faith within the site of struggle that is the contemporary postmodern era.